Development Competitiveness Model Of Village Owned Enterprises ( BUMDES) Through The Global Competition - Mohamad Nur Singgih (Publisher Cv. Inara, 2021)
The development of a tourist village is an option for BUMDes in Malang district as a driver of the local economy. The research objective is to analyze to compile the BUMDes model in developing competitiveness that has competitive advantages in the global market. Methods of data collection using interviews, questionnaires and observations with a research sample of 200 respondents taken by purposive sampling from tourists visiting 10 tourist villages in Malang district. The approach used in this research is mixed methods, including qualitative and quantitative methods to assess the competitiveness and factors that affect the performance of BUMDes. The analysis technique uses Structural Equation Modeling (SEM) to model tourism competitiveness in Malang district. The results showed that the competitiveness of tourism villages as indicated by the attractiveness (attractions), infrastructure, tourist facilities, accessibility and institutions significantly affected the competitiveness and increased performance of BUMDes in Malang district